Genetically Modified Organism-Free RNA Interference: Exogenous Application of RNA Molecules in Plants. Issue 1 (8th July 2019) - Dalakouras, Athanasios; Wassenegger, Michael; Dadami, Elena; Ganopoulos, Ioannis; Pappas, Maria L.; Papadopoulou, Kalliope
Abstract : The latest advances in the field exogenous application of RNA molecules in plants help to protect and modify them through RNA interference (RNAi).